Eutrophication homogenizes shallow lake macrophyte assemblages over space and time. Issue 9 (11th September 2018) - Salgado, Jorge; Sayer, Carl D.; Brooks, Stephen J.; Davidson, Thomas A.; Goldsmith, Ben; Patmore, Ian R.; Baker, Ambroise G.; Okamura, Beth
Abstract: Eutrophication is commonly implicated in the reduction in macrophyte species richness in shallow lakes. However, the extent to which other more nuanced measures of macrophyte diversity, such as assemblage heterogeneity, are impacted concurrently by eutrophication over space and time and the joint influences of other factors (e.g., species invasions and connectivity) remains relatively poorly documented. Using a combination of contemporary and paleoecological data, we examine how eutrophication influences macrophyte assemblage heterogeneity and how nutrient enrichment interacts with watercourse connectivity, lake surface area, and relative zebra mussel abundance over space (within and among lakes) and time (decades to centuries) at the landscape scale. The study system is the Upper Lough Erne, Northern Ireland, UK, which is composed of a large main lake and several smaller satellite lakes that vary in their hydrological connectivity to the main lake. By applying homogeneity analysis of multivariate dispersions and partial redundancy analysis, we demonstrate that contemporary lake macrophyte heterogeneity and species richness are reduced in lakes with intensified eutrophication but are increased in lakes with greater zebra mussel abundance and lake surface area. Watercourse connectivity positively influenced assemblage heterogeneity and explained larger proportions of the variation in assemblage heterogeneity than local environmental factors, whereas variation in species richness was better related to local abiotic factors. Macrophyte fossil data revealed within‐ and among‐lake assemblage homogenization post‐1960, with the main lake and connected sites showing the highest rates of homogenization due to progressive eutrophication. The long‐term and contemporary data collectively indicate that eutrophication reduces assemblage heterogeneity over time by overriding the importance of regional processes (e.g., connectivity) and exerts stronger pressure on isolated lakes. Our results suggest further that in connected lake systems, assemblage heterogeneity may be impacted more rapidly by eutrophication than species richness. This means that early effects of eutrophication in many systems may be underestimated by monitoring that focuses solely on species richness and is not performed at adequate landscape scales.